Staged single-port thoracoscopic R2 sympathicotomy as a reproducible, safe and effective treatment option for debilitating severe facial blushing. (14th October 2022) - van der Weijde, Emma; Kuijpers, Michiel; Bouma, Wobbe; Mariani, Massimo A; Klinkenberg, Theo J
Abstract: OBJECTIVES: Our goal was to investigate the safety, feasibility, success rate, complication rate and side effects of staged single-port thoracoscopic R2 sympathicotomy in the treatment of severe facial blushing. Facial blushing is considered a benign condition; however, severe facial blushing can have a major impact on quality of life. When nonsurgical options such as medication and psychological treatments offer no or insufficient relief, surgical treatment with thoracoscopic sympathicotomy should be considered. METHODS: All patients who underwent a staged thoracoscopic sympathicotomy at level R2 for severe facial blushing between January 2016 and September 2021 were included. Clinical and surgical data were prospectively collected and analysed. RESULTS: A total of 16 patients with low operative risk (American Society of Anesthesiologists class 1) were treated. No major perioperative complications were encountered. One patient experienced postoperative unilateral Horner's syndrome that resolved completely after 1 week. Two patients experienced compensatory hyperhidrosis. The success rate was 100%. One patient experienced a slight recurrence of blushing symptoms after 3 years that did not interfere with their quality of life. All patients were satisfied with the results and had no regrets of having undergone the procedure. CONCLUSIONS: Staged single-port thoracoscopic R2 sympathicotomy is a reproducible, safe and highly effective surgical treatment option with low compensatory hyperhidrosis rates and the potential to significantly improve quality of life in carefully selected patients suffering from severe facial blushing. We would like to increase awareness among healthcare professionals for debilitating facial blushing and suggest timely referral for surgical treatment. Abstract : Facial blushing is an expression of emotion caused by the activation of the sympathetic nervous system.